Obtaining and evaluation of the dogs sperm quality - Панасова, Т. Г.; Кулинич, С. М.; Жерносік, І. А.; Маленко, А. В. (Scientific Progress & Innovations, 2017)
Dogs semen was received by masturbation method in the presence and without a straw bitch, also evaluation of the quality of ejaculate was made by organoleptic, microscopic and microbiological methods. It was found that it is better to get dogs semen without straw bitch presence, some dogs are not suitable for artificial insemination due to inhibition of sexual reflexes in them. Dogs semen is not suitable for insemination of the bitches if a concentration of blood in it 0,140–0,147 billion/ml with an activity of 2–3 points and with the presence of microorganisms of the genus Staphylococcus in it.